Primary Ewing sarcoma/primitive neuroectodermal tumor of the lung - Devika Gupta; Tathagata Chatterjee; Rohit Tewari; Arti Trehan; Anuradha Ahuja (University of São Paulo, 2021)
We present the autopsy findings and differential diagnosis in a 42year old male who presented with fever and rapidly progressive respiratory symptoms like breathlessness, nonproductive cough and right sided chest pain. Initial imaging workup done at our hospital revealed a large unilateral tumor with tracheal shift. While being evaluated patient developed facial puffiness, tachypnea suggestive of superior vena cava obstruction. Antemortem biopsy of lung mass was attempted twice and that suggested malignant lesion. Unfortunately, the individual had a rapid downhill course following admission. Post mortem examination was conducted that on opening the thoracic cavity revealed total replacement of right lung tissue by a necrotic growth which was deeply adherent to the rib cage. The contralateral lung as well as all other visceral organs were unremarkable grossly. Histopathology confirmed primary Ewing sarcoma of the lung. We hereby, report a rare case of primary lung Ewing sarcoma diagnosed at autopsy.